THE EVALUATION PROCESS: BASIS FOR ITS IMPLEMENTATION IN THE PSYCHIATRIC NURSING TEACHING - Margarita A. Villar Luis (Universidade Federal do Paraná, 1998)
This paper presents some considerations about evaluation in teaching in order to point out theoretical statements that gave basis to a guideline proposed to evaluate the students on the courses which emphasize the psycho aspects of patients, especially the psychiatric nursing course.